Color Brightness Enhancement in Komet Fish (Carassius auratus) By Giving Different Carrot Flour Doses - Nurrahma Nurrahma; Mulyadi Mulyadi; Usman M Tang (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This study aims to determine of this the best dose of carrot flourin increasing the brightness ofcolorCarassiusauratus. The method ofthis research was using the experimental method with Completely Randomized Design(CRD) by using one factor of 4 treatment levels and 3 replications. The treatments each dose of carrot flour were using0% (control), 5%, 7% and 9%. The fry size was around 3-4 cmthen reared in the aquarium by 15 L of water and 10 fishes ofstocking density each aquarium. The fish were reared for 40 days, three times a day of feeding frequency. The results showed that thebest treatment wasP4 dose of carrot flour 9%by giving absolute thebest color brightness with value 11,73, weight growth for 1.59 g, absolutelongevity for 1.57 cmand fish survival for 100%. The conclusion is different dose of carrot flour significantly affect the color brightnessandgrowth performance ofCarassiusauratus. Keywords: Daucus sp.; Color quality;Growth;Carassiusauratus.